An investigation into the characteristics of teacher professionalism in a Chinese higher educational institution - Li, Jia (2019)
This qualitative research seeks to investigate the characteristics of construction and enactment of teacher professionalism and its changes, through a qualitative study carried out in a Chinese higher educational institution. To achieve this, the study examined the factors contributing to the formation and change of the characteristics based on the three rounds of semi-structured interviews with fifteen participants from a University in China. The findings show that teachers‘ professional responsibility is a multi-faceted and relatively stable concept and plays an important role in their perceptions of professionalism. The findings also reveal that factors including personal biography, institutional environment and social culture intertwine to shape the formation, fluctuation and development of responsibility. In addition, the study reveals that responsibility is an expression of a particular professional identity and identity is an indication of the strength of responsibility. Both professional responsibility and identity serve as important integral aspects of professionalism. Moreover, teacher professional responsibility has significant impact on teacher passion and agency in enacting professionalism and professional development. The research contributes to a more nuanced understanding of teacher professionalism by identifying teacher professional responsibility as the core element of professionalism in the context of Chinese higher education. This research also serves to add knowledge about, and advance the understanding of professional responsibility, identity and professionalism by uncovering explicit connections among them. This research has important implications for higher education front-line teachers by developing their awareness of the importance that needs to be attached to the maintenance and development of professional responsibility. It also serves to raise university policy makers' awareness of the significant influence the leadership, nature of institution and policies could exert on teachers and to suggest that leaders re-examine the way they design policy and the support they provide to the teachers.